2020
DOI: 10.3389/fendo.2020.00554
|View full text |Cite
|
Sign up to set email alerts
|

Practical Considerations for the Management of Cushing's Disease and COVID-19: A Case Report

Abstract: , is experiencing the corona virus disease 2019 (COVID-19) pandemic that may present as an acute respiratory infection. We report on COVID-19 pneumonia in the context of a complex case of Cushing's disease (CD). Case Report: A 67-year-old man with CD, who was admitted to our hospital, presented with signs and symptoms of adrenal insufficiency with persistent hypotension and glycemia toward the lower limits. We progressively withdrew almost all treatments for diabetes and CD (pasireotide and metyrapone), and i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
(27 reference statements)
0
25
0
2
Order By: Relevance
“…Onset of adrenal failure in a patient with Cushing disease due to a relapsing ACTH-secreting pituitary macroadenoma and COVID-19 pneumonia on treatment with metyrapone and cabergoline was reported. A potential confounding role of enoxaparine used to control the hypercoagulable state in the genesis of persistent hyperkalemia after correction of adrenal insufficiency, due to suppressive effect on aldosterone production was suggested [ 117 ].…”
Section: Pituitary Conditions and Covid-19mentioning
confidence: 99%
“…Onset of adrenal failure in a patient with Cushing disease due to a relapsing ACTH-secreting pituitary macroadenoma and COVID-19 pneumonia on treatment with metyrapone and cabergoline was reported. A potential confounding role of enoxaparine used to control the hypercoagulable state in the genesis of persistent hyperkalemia after correction of adrenal insufficiency, due to suppressive effect on aldosterone production was suggested [ 117 ].…”
Section: Pituitary Conditions and Covid-19mentioning
confidence: 99%
“…Pasireotide and metyrapone and DM treatment were halted, and injectable GC was started. Furthermore, unexpected hyperkalemia in CS patients under treatment with heparin, as was the case in this patient, might be a signal of aldosterone suppression and increased awareness for electrolyte abnormalities is needed (23).…”
Section: Cushing's Disease (Cd)mentioning
confidence: 85%
“…The patient improved clinically and underwent curative surgery 1 month later (after testing negative for COVID-19) (22). Beretta et al, reported on a case of a 67-year-old male with CD, who presented with signs and symptoms of AI; (persistent hypotension and hypoglycemia) after he became infected with COVID-19 (23). Pasireotide and metyrapone and DM treatment were halted, and injectable GC was started.…”
Section: Cushing's Disease (Cd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of COVID-19 in a patient with preexisting adrenostatic therapy, stress doses of GCs should be given to prevent critical illness-related corticosteroid insufficiency [58]. There is also a clinical case of a 67-yearold man with Cushing's disease receiving pasireotide and metyrapone, who developed adrenal insufficiency during COVID-19 infection requiring GC replacement therapy [65]. 'Block and replace' regimens can be useful in certain situations [58,59].…”
Section: Considerations For Patients With Endogenous Cushing's Syndromementioning
confidence: 99%